Aortic Valve Stenosis: Diagnostic Approaches and Recommendations of the 2021 ESC/EACTS Guidelines for the Management of Valvular Heart Disease –A Review of the Literature - Rana, Mukaram (Cardiology and Cardiovascular Medicine, 2022)
Aortic stenosis (AS) is the most common valvular heart disease in Europe and North America requiring a surgical or interventional treatment. Due to demographic changes with an aging population the burden of valvular heart diseases and especially the importance of aortic stenosis (AS) will be growing in future. As the onset of symptoms is associated with a decrease in life expectancy appropriate and early diagnosis are of utmost importance. However, insights of clinical practice underline diagnostic challenges which may lead to a delayed initiation of treatment with an adverse effect on the prognosis. The aim of this review is to display different diagnostic approaches that may be helpful in detecting patients with aortic valve stenosis. This review will focus on both non-invasive and invasive diagnostic approaches that can be implemented in clinical routine. Further-more, we will especially highlight recommendations of the 2021 European guidelines for the management of valvular heart disease. Methods: For this review a selective literature research on the databases PubMed and Google Scholar was conducted. Original articles, reviews and meta-analyses were included when meeting our search criteria. Following terms were used in different combinations: Aortic valve stenosis; Aortic stenosis; diagnosis of aortic stenosis; ESC Guidelines